(untitled) (Ozone Therapy Global Journal, 2023)
Ozone therapy is a technology that is currently being used in the treatment of a wide variety of diseases, with increasing diffusion in the medical field. One of the most widely used techniques to transfer ozone to a patient consists of bubbling ozone at low concentrations into a saline solution and injecting it into the patient. Objective: to analyze the efficiency of the ozonation technique of a saline solution under micro-bubbling/nano-bubbling in a closed glass device system: its advantages compared to the ozone dose that is finally transferred to the patient intravenously and its benefits in applications in medicine and dentistry. Method: For the study, ozone was micro-bubbled at different standardized concentrations in a closed glass device, specially designed for this purpose, with saline solution (NaCl 0.9%) and then passed through an ozone concentration analyzer in liquids. brand BMT964 AQ-LC, Messtechnick GmbH, (Germany), for an Anseros® spectrophotometer model OZONE MONITOR GM-RTI® (Germany) and a Mass Spectrophotometer, (GCMS). Two ozone generators were used: the Ozonobaric P® Sedecal® (Spain) and the Ozonette® Sedecal® (Spain) The first and second parts of the study were carried out at CSI ANALITICA SL, Tres Cantos, Madrid, Spain. https://www.csianalitica.com Results: After 5 min of ozone micro-bubbling, the solution became saturated. 25% ozone was dissolved in the saline solution. Post saturation, the ozone concentration in the solution remained stable for 30 minutes without bubbling. Technical conclusions: The preparation of the micro bubbled solution is carried out more quickly, saving time, oxygen and equipment wear. By keeping the ozone concentration stable in the post-saturation solution under micro-bubbling, for 30 min without bubbling, the administration to the patient can be carried out without bubbling. What allows to release the generator, save time, oxygen and time to the operator.